Lateral Graphene‐Contacted Vertically Stacked WS2/MoS2 Hybrid Photodetectors with Large Gain. Issue 46 (17th October 2017) - Tan, Haijie; Xu, Wenshuo; Sheng, Yuewen; Lau, Chit Siong; Fan, Ye; Chen, Qu; Tweedie, Martin; Wang, Xiaochen; Zhou, Yingqiu; Warner, Jamie H.
Abstract: A demonstration is presented of how significant improvements in all‐2D photodetectors can be achieved by exploiting the type‐II band alignment of vertically stacked WS2 /MoS2 semiconducting heterobilayers and finite density of states of graphene electrodes. The photoresponsivity of WS2 /MoS2 heterobilayer devices is increased by more than an order of magnitude compared to homobilayer devices and two orders of magnitude compared to monolayer devices of WS2 and MoS2, reaching 10 3 A W −1 under an illumination power density of 1.7 × 10 2 mW cm −2 . The massive improvement in performance is due to the strong Coulomb interaction between WS2 and MoS2 layers. The efficient charge transfer at the WS2 /MoS2 heterointerface and long trapping time of photogenerated charges contribute to the observed large photoconductive gain of ≈3 × 10 4 . Laterally spaced graphene electrodes with vertically stacked 2D van der Waals heterostructures are employed for making high‐performing ultrathin photodetectors. Abstract : WS2 /MoS2 vertical heterostructures are known to have type‐II band alignment and form layer‐separated electron–hole pairs upon illumination. Lateral photodetectors based on WS2 /MoS2 heterostacks with graphene electrodes are demonstrated using crystals grown by chemical vapor deposition. The unique device architecture results in superior photosensing performance with large photoconductive gain due to long‐lived interlayer excitons and the photogating mechanism.